Demographic and clinical factors associated with psychiatric inpatient admissions during the COVID-19 pandemic. (April 2022) - Seiler, Natalie; Ng, Matthew; Dawud, Midya; Das, Subhash; Ooi, Shu-Haur; Waterdrinker, Astrid
Objective: The COVID-19 pandemic may cause a major mental health impact. We aimed to identify demographic or clinical factors associated with psychiatric admissions where COVID-19 was attributed to contribute to mental state, compared to admissions which did not. Methods: A retrospective cohort study was undertaken of inpatients admitted to Northern Psychiatric Unit 1, Northern Hospital in Melbourne, Victoria, Australia during 27/02/2020 to 08/07/2020. Data were extracted for participants who identified COVID-19 as a stressor compared to participants who did not. Fisher's exact test and Mann-Whitley rank sum test were used. Results: Thirty six of 242 inpatients reported the COVID-19 pandemic contributed to mental ill health and subsequent admission. Reasons given included social isolation, generalized distress about the pandemic, barriers to support services, disruption to daily routine, impact on employment, media coverage, re-traumatization, cancelled ECT sessions, loss of loved ones, and increased drug use during the lockdown. Chronic medical conditions or psychiatric multimorbidity were positively associated and smoking status was negatively associated with reporting the COVID-19 pandemic as a contributor to mental ill health. Conclusion: Screening and identifying vulnerable populations during and after the global disaster is vital for timely and appropriate interventions to reduce the impact of the pandemic worldwide.